2023
DOI: 10.3389/fpls.2023.1107954
|View full text |Cite
|
Sign up to set email alerts
|

Temperature affects organic acid, terpene and stilbene metabolisms in wine grapes during postharvest dehydration

Abstract: The partial dehydration of grapes after harvest is a traditional practice in several winegrowing regions that leads to the production of high quality wines. Postharvest dehydration (also known as withering) has a significant impact on the overall metabolism and physiology of the berry, yielding a final product that is richer in sugars, solutes, and aroma compounds. These changes are, at least in part, the result of a stress response, which is controlled at transcriptional level, and are highly dependent on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The most significant change was recorded for terpinen-4-ol which was increased by 63 folds in WL30 blueberry wines (Table S3). In agreement with our findings, previous studies have characterized terpinen-4-ol as a marker of grape postharvest dehydration (Negri et al, 2017; Shmuleviz et al, 2023). Furthermore, the rOAV of terpinen-4-ol in CK was lower than 0.1 but higher than 1 in WL30 blueberry wines, suggesting that the aroma contribution of terpinen-4-ol was substantially enhanced in blueberry wines produced from dehydrated berries (Table S3).…”
Section: Resultssupporting
confidence: 93%
“…The most significant change was recorded for terpinen-4-ol which was increased by 63 folds in WL30 blueberry wines (Table S3). In agreement with our findings, previous studies have characterized terpinen-4-ol as a marker of grape postharvest dehydration (Negri et al, 2017; Shmuleviz et al, 2023). Furthermore, the rOAV of terpinen-4-ol in CK was lower than 0.1 but higher than 1 in WL30 blueberry wines, suggesting that the aroma contribution of terpinen-4-ol was substantially enhanced in blueberry wines produced from dehydrated berries (Table S3).…”
Section: Resultssupporting
confidence: 93%
“…Taking advantage of the experimental plan from a recent study ( Shmuleviz et al , 2023 ), we analyzed the expression of NAC61 in grape berries subjected to post-harvest dehydration in two different temperature regimens. The results showed that NAC61 expression is significantly induced by high temperature, similar to its HCT MYB14 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Vitis vinifera cv. ‘ Corvina’ berries (mature and low-/high-temperature dried) were collected for cDNA preparation and transcriptomic analysis ( Shmuleviz et al , 2023 ). Vitis vinifera cv.…”
Section: Methodsmentioning
confidence: 99%
“…Vitis vinifera cv. 'Corvina' mature and low/high temperature dried berries cDNA was previously prepared by (Shmuleviz et al, 2023).…”
Section: Real Time Quantitative Polymerase Chain Reaction (Rt-qpcr)mentioning
confidence: 99%
“…Taking advantage of the experimental plan from a recent work (Shmuleviz et al, 2023), we analyze the expression of NAC61 in grape berries subjected to post-harvest dehydration in two different temperature regimes. The results show that NAC61 expression is significantly induced by high temperature, similarly to its HCT MYB14 (Fig.…”
Section: Nac61 Expression Is Enhanced By High Temperature and Botryti...mentioning
confidence: 99%